Enhanced defect annihilation capability of the graphene/copper interface: An in situ study. (October 2021) - Yang, K.M.; Tang, P.Z.; Zhang, Q.; Ma, H.Y.; Liu, E.Q.; Li, M.; Zhang, X.; Li, Jin; Liu, Y.; Fan, T.X.
Abstract: It is well known that energetic heavy ion irradiations can often induce defects and ultimately lead to material degradations. Interfaces, such as high-angle grain boundaries (HAGBs), are generally used as defect sinks for alleviating the irradiation damage. However, HAGBs are often unstable during radiation. Here we investigate the interfacial irradiation responses of the graphene (Gr)/Cu composites by using in situ Kr ++ ions irradiation under transmission electron microscopy. The results revealed that the Gr/Cu interface exhibits higher defect annihilation capability compared to the HAGBs in Cu. Moreover, the atomistic simulations suggested a slightly higher and larger range of stress field for the Gr/Cu interface, which contributes to the enhanced defects absorption capability. The present findings are essential to understand and design a new class of carbon/metal composites with superior irradiation tolerance. Graphical abstract: Image, graphical abstract